Pengembangan Aplikasi Customer Relationship Management Donatur Panti Yauma Berbasis Web Menggunakan Framework Laravel - Aef Syaefuddin Zuhri; Budiman (LPPM Universitas PGRI Adi Buana, 2024)
Yayasan Umat Mandiri Nusantara (Panti Yauma) plays an important role in humanitarianactivities and social services, with significant contributions from donors. To improve theefficiency of managing relationships with donors, an effective and centralized system is needed.This research developed a web-based Customer Relationship Management (CRM) Applicationspecifically for donors of the Yauma Home. This application, which uses the Laravel Framework,is designed to make it easier for admins to manage donation history, record donations, anddisplay donor data. Key features include donor management, donation recording, and donationreporting. Testing shows that the app improves efficiency and transparency in managingdonations and makes it easier for donors to track their contributions. With this technology, it ishoped that the relationship between the foundation and donors can be better and sustained.Keywords: CRM; Laravel; Donors; Yauma Orphanage; Information Technology Yayasan Umat Mandiri Nusantara (Panti Yauma) berperan penting dalam kegiatan kemanusiaandan pelayanan sosial, dengan kontribusi signifikan dari para donatur. Untuk meningkatkanefisiensi pengelolaan hubungan dengan donatur, diperlukan sistem yang efektif dan terpusat.Penelitian ini mengembangkan Aplikasi Customer Relationship Management (CRM) berbasis webkhusus untuk donatur Panti Yauma. Aplikasi ini, yang menggunakan Framework Laravel,dirancang untuk memudahkan admin dalam mengelola riwayat donasi, perekapan donasi, danmenampilkan data donatur. Fitur utama mencakup manajemen donatur, pencatatan donasi, danpembuatan laporan donasi. Pengujian menunjukkan bahwa aplikasi ini meningkatkan efisiensidan transparansi dalam pengelolaan donasi serta memudahkan donatur melacak kontribusimereka. Dengan teknologi ini, diharapkan hubungan antara yayasan dan donatur dapat terjagadengan lebih baik dan berkelanjutan.Kata kunci: CRM; Laravel; Donatur; Panti Yauma; Teknologi Informasi.